The German labor market response in the world recession – de-mystifying a~miracle - Joachim Möller (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
This paper aims at analyzing the astonishingly mild response of the German labor market to the severe demand shock that occurred in the aftermath of the financial crisis. It stresses the role of institutions such as working-time accounts which create a large scope for a buffering capacity within the firm. It is argued that labor market reforms and the behavior of social partners have strengthened the adjustment possibilities when facing a temporary slump. The crisis mainly affected export-oriented manufacturing firms in Germany's thriving regions. Before the crisis those firms were the engines of growth and suffered from a shortage of qualified professional workers. Moreover, training costs are relatively high and dismissals would entail a significant loss in firm-specific human capital. Supported by the generous short-time work schemes, these factors contributed to the high willingness of crisis-stricken firms to pursue a strategy of massive labor hoarding. By contrast, the comparatively high employment protection does not seem to play a major role in explaining the adjustment behavior of German firms in the current crisis.
Keywords: J2; J6; 330; Arbeitsmarktentwicklung; Rezession; Finanzkrise; Bruttoinlandsprodukt; Beschäftigungsentwicklung; institutionelle Faktoren; Kurzarbeit; Arbeitszeitkonto; Humankapital; Kurzarbeitergeld; Kündigungsschutz